Mid-Term Clinical Outcome and Reconstruction of Posterior Tibial Slope after UKA - Franz, Alois; Boese, Christoph Kolja; Matthies, Andrej; Leffler, Jörg; Ries, Christian (The Journal of Knee Surgery, 2019)
Unicompartmental knee arthroplasty (UKA) has gained growing popularity over the last decades. The posterior tibial slope (PTS) has been shown to play a significant role for knee biomechanics and is thought to be crucial for clinical function of the UKA. We evaluated the clinical outcome at mid-term follow-up after UKA. Furthermore, the reconstruction of the individual PTS was analyzed. A total of 91 consecutive patients undergoing medial UKA for osteoarthritis were included. Patients were contacted by telephone for a survival analysis at a minimum of 30 months after surgery. Patient-oriented questionnaires and Knee Osteoarthritis Outcome Score (KOOS) were obtained. A retrospective chart review and radiological analysis of component alignment were performed for all patients before and at 6 weeks after surgery. Of 91 patients (93 knees) undergoing UKA, 69 patients (70 knees) were available for clinical follow-up after a mean of 56.0 (range 31–81) months post-surgery. The clinical results of the examined patients in the present study showed mean subscale scores of the KOOS and Western Ontario and McMaster Universities Osteoarthritis Index between 71 and 91%. Overall 7 of 91 patients were revised during the course of follow-up period and underwent total knee arthroplasty. A Kaplan–Meier analysis showed a survival rate for UKA of 90.5% after 48 months. Calculated implant survival was 75.9 months (95% confidence interval 72.3–79.6) at the mean. The radiographic analysis of pre- and postoperative PTS showed no differences (p = 0.113).UKA for osteoarthritis of the medial knee compartment shows encouraging clinical results at mid-term follow-up. The individual PTS could be reconstructed within acceptable ranges. This is a retrospective therapeutic study with Level IV.
Keywords: unicompartmental knee arthroplasty; all-polyethylene; metal-backed; tibial component; posterior tibial slope